Integration site features for the Acute UD, Acute UD + 5 and Chronic UD cohorts. - Tine Struyve (22683295) (2025)
Individuals are categorized into groups accordingly to the stage when ART was initiated. Donut charts display the number of integration sites (IS) color-coded by their respective characteristic at UD and UD + 5. Distinct clonal populations of infected cells are represented by different patterns. The total number of IS generated by ISLA for each participant is shown in the middle of each donut. (TIF)